ASSESSMENT OF BIOLOGICAL CONDITION OF GYPSIFEROUS SOILS BY DEHYDROGENASE ACTIVITY - Abdullaeva Kh.; Makhkamova D.; Iskhakova Sh.; Pulatov B. (Web of Journals Publishing, 2025)
The article deals with enzymatic activity of gypsum-bearing soils of Jizzak region, characterised by high content of gypsum (20-30 %) and diversity of its morphological forms - from fine crystalline in auxiliary horizons to coarse crystalline in groundwater zone. These soils occupy significant areas of terrace complexes of the region. It was found that enzymatic activity, in particular the activity of dehydrogenase, a sensitive intracellular enzyme, is closely correlated with the level of hypsification and type of agrocenosis. Dehydrogenase serves as an informative bioindicator reflecting the general biological state of soils and intensity of microbiological processes, especially in conditions of gypsum and saline ecosystems.
Keywords: Dehydrogenase activity, gypsiferous soil, soil biological activity, enzymatic activity,soil microorganisms, bioindication of degradation, ecological soil assessment, oxidoreductase enzymes, agroecosystems, soil salinization and gypsum content.